Amygdala Functional Connectivity and Negative Reactive Temperament at Age Four Months - Filippi, Courtney A. (J Am Acad Child Adolesc Psychiatry, 2020)
OBJECTIVE: Infant amygdala connectivity correlates with maternal reports of infant temperament characterized by novelty-evoked distress and avoidance. However, no studies examine how human infant amygdala connectivity relates to direct observations of novelty-evoked distress in human infants. The current study examines the link between amygdala connectivity and infant novelty-evoked distress using direct-observation of temperament. METHOD: At four-months of age infants’ (N=90) novelty-evoked distress was assessed using a standardized reactivity assessment and parent-report. Within three weeks, resting state fMRI was collected in a subset of infants (n=34). Using a whole-brain voxel wise approach, we examine amygdala connectivity associated with positive and negative affect during the reactivity assessment. We then examined regions where the association of amygdala connectivity with negative affect was higher than with positive affect. Additionally, we examined associations between amygdala connectivity and parent-report of temperament. RESULTS: Greater amygdala-cingulate and amygdala-superior frontal gyrus connectivity was associated with lower positive affect during the reactivity assessment. Results further indicated that the association between amygdala-cingulate connectivity was greater for negative affect compared to positive affect. There were no significant associations between latency to approach novelty (as measured by parent-report) and amygdala connectivity. Validation analyses conducted using a large independent longitudinal sample (N=323) demonstrate that negative reactivity is associated with increased child-reported anxiety symptoms in adolescence. CONCLUSION: These results provide novel insight into the developmental pathophysiology of novelty-evoked distress. This is consistent with research linking an altered cognitive control mechanism to temperamental risk for anxiety.